Predictors of Psychological Burnout Among Jordanian University Students: Multicenter Cross-Sectional Study - Othman A. Alfuqaha; Randah O. Barakat; Uday M. Al-masarwah; Dua’a A. Aladwan; Ayman O. Baniamer (Education Sciences)
(1) Background: Psychological burnout (BO) is one of the most significant challenges faced by university students. This study aimed to explore the perceived levels of BO, psychological resilience (PR), and psychological hardiness among university students in Jordan. It also investigated the factors that may contribute to psychological BO. (2) Methods: Using a cross-sectional design, a total of 1219 university students (female = 933 (76.5%), male = 286 (23.5%)) were conveniently selected from four universities (two public and two private) to represent the study sample. (3) Results: Results found that 40.39% of university students had severe psychological BO levels, although most of them had acceptable PR (92.74%) and hardiness (83.7%) levels. Unmarried students at public universities, medical schools, and fourth-year students or beyond showed higher levels of psychological BO than any other category. A negative correlation (p < 0.05) was observed among psychological BO and both perceived PR and hardiness variables. Additionally, a positive correlation was found between perceived PR and psychological hardiness. Significant contributions of hardiness, university type, and academic year to BO were detected, with a variance of 29.7%. (4) Conclusions: Academic teachers and policymakers should tackle this problem among university students to help alleviate the different sources of stressors in university life.